Sarcoidosis in Black Women in the United States: Data From the Black Women’s Health Study - Cozier, Yvette C. (American College of Chest Physicians, 2011)
BACKGROUND: Sarcoidosis is a systemic granulomatous disorder of unknown cause that occurs among men and women of all races. In the United States, black women are most frequently and most severely affected. There have been few epidemiologic studies of sarcoidosis focusing on black women. METHODS: In this article, we present data on incidence, prevalence, and clinical characteristics of sarcoidosis among participants in the Black Women’s Health Study, a cohort study of 59,000 black women from across the United States. Data on incident disease and potential risk factors are obtained through biennial questionnaires. Follow-up has been > 80% through six completed cycles. RESULTS: There were 685 prevalent cases of sarcoidosis at baseline in 1995 and 435 incident cases reported during 611,585 person-years of follow-up through 2007, for an average annual incidence rate of 71/100,000 and a current prevalence of 2.0%. The sarcoid diagnosis was confirmed in 96% of self-reported cases for whom medical records or physician checklists were obtained. The most frequently affected site was the lung. Most patients also had extrapulmonary involvement, with the most common sites being lymph nodes, skin, and eyes. Prednisone had the highest prevalence of use, followed by inhaled corticosteroids. CONCLUSIONS: This study confirms previous reports of high incidence and prevalence of sarcoidosis among black women, as well as the extent of extrapulmonary disease, frequent need for steroid therapy, and comorbid conditions in this population. The prospective identification of sarcoidosis cases from a defined population will enable a valid assessment of risk factors for incident disease as follow-up continues.